Reflection of statistical nature of steel strength in steel structures standards - Hudz, Serhii; Horb, Oleksandr; Pents, Volodymyr; Dariienko, Viktor (Academic journal Industrial Machine Building Civil Engineering, 2020)
The main stages of creating a spatial model of the steel frame are considered for industrial buildings or warehouses with a pitched roof. Different approaches to the analysis of internal forces of the first and second orders and the stability calculation for steel elements of building structures under the combined action of compression and transverse bending are highlighted using software applications. Ways to improve the process of creating a calculation model, design documentation, and working drawings are outlined. A comparison of specialized software products for calculating building models with portal frames (Autodesk Robot Structural Analysis Professional, PortalPlus, Consteel, Tekla Structural Designer, and Dlubal RFEM) is presented. Their advantages and disadvantages are indicated
Keywords: software; spatial model; portal frame; buckling; restraint